Vipos application development design - Heriyanto; Verdi Yasin; Akmal Budi Yulianto (Journal of Engineering, Technology and Computing (JETCom), 2022)
A good communication within the company requires a good and optimal information system. Especially in information systems related to customer relations to management called CRM (Customer Relationship Management) in the company. Customer data is the main data that is important to be developed in the business of a company, especially a business engaged in the service sector. If the customer data has not been thoroughly processed, the customer data will have no function and have no effect on the progress of the company. Because of the very important function of this module, customer data is the most important data needed and can be developed for business continuity in general. The importance of processing customer data, researchers will design the development of the Vipos application at PT Amarta Eksis Digdaya which focuses on the customer relationship management module with the Pieces Method. The Pieces method consists of several stages which include Performance, Information, Economy, Control, Efficiency, and Service which are techniques for identifying and solving problems that have occurred in information systems. The conclusion of this analysis resulted in the identification of the main problems of a system and provide solutions to these problems.